Embedding CoPt magnetic nanoparticles within a phosphate glass matrix - Orives, Juliane Resges [UNESP]; Viali, Wesley Renato [UNESP]; Destro, Fabrício Benedito; da Silva, Sebastião W.; Ribeiro, Sidney J.L. [UNESP]; Nalin, Marcelo [UNESP] (Elsevier, 2020)
Glasses are materials with highly flexible compositions and high chemical and physical durability. These characteristics make them suitable materials for hosting nanoparticles for different purposes. Hybrid glasses containing magnetic nanoparticles have been highlighted due to their potential for application as ultra-sensitive magnetic sensors and magnetic devices. In this work, phosphate bulk glasses containing 0.5%, 1.0%, and 2.0% in mass of metallic CoPt alloy nanoparticles were prepared by melt-quenching technique. The CoPt nanoparticles were synthesized by reducing metal precursors in a high temperature organic solvent and, in the second step, they were covered with a silica layer in order to protect the nanoparticles for the subsequent melting. The nanoparticles were treated at different temperatures. Heat treatment at 900 °C showed the highest values of saturation magnetization and coercivity, and for that reason these nanoparticles were chosen for incorporation into glass. In the transmission electron microscopy images of the glass containing 2.0% in mass of nanoparticles, the interplanar distance of 0.21 nm was identified and indexed to the 111 plane of CoPt, confirming that the nanoparticles were successfully embedded into the matrix. The UV–Vis spectra presented Co2+ characteristic bands at 528, 578, and 626 nm, indicating that these ions are tetrahedrally coordinated in the matrix. Themagnetic measurements presented behavior close to ferromagnetic, showing that it is possible to prepare a magnetic glass containing bimetallic nanoparticles.
Keywords: Coacervate; Cobalt platinum alloy; Hybrid materials; Magnetic glass; Magnetic nanoparticles